Pengaruh Pemberian Bubur Tempe Beras Putih Dan Bubur Tempe Beras Merah Terhadap Peningkatan Berat Badan Baduta Gizi Kurang Di Wilayah Kerja Puskesmas Arjasa Kabupaten Jember - Tita Rudini Yassin (Jurnal Gizi Prima (Prime Nutrition Journal), 2017)
Background. Nutrition problems in children under five in Indonesia have undergone improvements. This can be seen, among others, from the decrease in the prevalence of malnutrition in children under five from 5.4% to 4.9% in 2010. Despite the decline, the nominal number of malnourished children is still relatively large, therefore intensive treatment to overcome that matter. Research Methods. The research design used was quantitative with the design of one group pre test post test. Research Result. The increase in body weight in the red rice porridge treatment group was much higher compared to the average value of weight gain in the treatment group giving white rice porridge. Conclusion. The treatment of porridge of brown rice tempe to increase body weight in children is considered quite effective.